Kriteria Rumah Tinggal Ideal Bagi Pengrajin Gerabah di Desa Panjangrejo, Kabupaten Bantul, D.I. Yogyakarta - Sidhi Pramudito; Yustina Banon Wismarani (RUAS (Review of Urbanism and Architectural Studies), 2020)
Panjangrejo village is a tourism village that located in Pundong sub-district, Bantul regency, Yogyakarta Special Region. This village is an area of pottery production centers where most of the villagers work as pottery craftsmen. This potential is also supported by the Regional Planning and Development Agency (Bappeda) and the Bantul Regency Tourism Office which establishes the village as one of the priority planning of 7 (seven) priority tourism villages in Bantul Regency in 2019. Research on the criteria of ideal housing can become one of the first steps to understanding the urge and needs of pottery craftsmen of houses. The purpose of this study is to determine the criteria that are the preferences of respondents about an ideal houses. This research uses a qualitative approach by collecting data through a questionnaire distributed to pottery craftsmen. Data analysis was performed by text data analysis. The results of the analysis showed that of the various criteria about the ideal houses, the dominant design criteria found were aspects of environmental health of the house, the form and finishing of the house, the spatial needs and relationships, and building construction. The results of this study are also expected to be used as input for Bappeda and the Bantul Regency Tourism Office if in the future they will carry out planning and design in Panjangrejo Tourism Village.